Comparison of Sentinel-1A Ascending and Descending Image Processing Results on the Tukul Dam Using SNAP Software - Faiz Mahbubi; Sukamta; Prasetyo, Yudo (Universitas Negeri Semarang, 2025)
This study analysed and compared the accuracy of the results of Sentinel 1A satellite image processing in the ascending and descending orbit directions with SNAP software. The research is located at Tukul Dam, Karanggede Village, Arjosari District, Pacitan Regency, East Java Province, with a range of observation data for one year in 2022-2023. Sentinel 1A satellite image processing uses the Differential Interferometry Synthetic Aperture Radar (DInSAR) method. The results of Sentinel 1A image processing were validated using measurement data from 38 dam surface measurement points that had been measured terrestrial. The accuracy calculation uses the Root Mean Square error (RMSe) to measure the vertical movement of coordinates (Z) from the results of Sentinel 1A image processing in the ascending and descending orbit directions with the actual position in the field measured terrestrially. The result is the RMSe value of vertical movement from the Sentinel 1A image processing in the ascending direction is 0.015m. In comparison, the result of Sentinel lA image processing in the descending orbit direction is 0.234m. Based on the calculation results of the RMSe value of vertical movement, the results of Sentinel 1A image processing in the ascending direction are better used for calculating vertical movement at Tukul Dam.